Widefield ultrastable heterodyne interferometry using a custom CMOS modulated light camera - Patel, Rikesh; Clark, Matt; Achamfuo-Yeboah, Samuel (2011)
A method of detecting optical heterodyne interference fringes using a custom CMOS modulated light camera array has been developed. Widefield phase images are generated using quadrature demodulation and are kept stable using a feedback system. © 2011 OSA